Analysis of No-Repeat-Grade Policy in Schools: A Theoretical Review and Implications for Students’ Learning Motivation - Ilhamsyah, Rizal; Khairunnisa, Salsabila (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2024)
The no-repeat-grade policy in Indonesia aims to enhance accessibility and equality regarding education for students in primary schools, by offering opportunities for students to continue to move up even if their academic grades do not meet the set standards. This study aims to analyze the impact of the policy on student learning motivation through literature review. Using the library research method, this study collects and analyzes literature related to policies without leaving the classroom and learning motivation theory. The results of the study show that this policy has double implications for student learning motivation. On the one hand, students feel safer and less stressed by the threat of failure, which can increase their intrinsic motivation. However, on the other hand, this policy has the potential to reduce extrinsic motivation, as students no longer feel threatened by exams or failures that affect their graduation. This decrease in external motivation can have an impact on the quality of long-term learning. Therefore, to maintain students’ motivation to learn, there needs to be adjustments in teaching methods and the role and support of parents and teachers in creating challenges that remain relevant. This research contributes to understanding the impact of the policy without leaving the classroom on students’ learning motivation, as well as recommendations for more effective policy implementation.